Wireless technologies for telemedicine - Ng, H. S.; Sim, M. L.; Tan, C. M.; Wong, C. C. (Kluwer Academic Publishers-Consultants Bureau, 2006)
Wireless telemedicine is a new and evolving area in telemedical and telecare systems. Healthcare personnel require realtime access to accurate patient data, including clinical histories, treatments, medication, tests, laboratory results and insurance information. With large-scale wireless networks and mobile computing solutions, such as cellular 3G, Wi-Fi mesh and WiMAX, healthcare personnal can tap into vital information anywhere and at any time within the healthcare networks. The recent introduction of pervasive computing, consisting of radio frequency identification (RFID), Bluetooth, ZigBee, and wireless sensor networks, further extends the potential for exploitation of wireless telecommunications and its integration into new mobile healthcare delivery systems.